Social reading : platforms, applications, clouds and tags /: platforms, applications, clouds and tags. (2013) - Cordón García, José Antonio; Alonso Arévalo, Julio; Gómez Díaz, Raquel; Linder Molin, Daniel Peter
No abstract available